Kemampuan Number Sense Siswa SMP berdasarkan Gender - Nourma Pramestie Wulandari; Tabita Wahyu Triutami (Griya Journal of Mathematics Education and Application, 2022)
Number sense ability is a basic skill that must be mastered by students at various levels of education. Number sense is concerned with one's sensitivity to numbers and flexibly using them in calculations and to solve given problems, both in mathematics and in everyday life. Number sense is very important to be mastered by students in facing the numeracy test in the Minimum Competency Assessment. This study aims to investigate the number sense ability of junior high school students based on gender. The research method used is descriptive quantitative with 80 grade IX junior high school students as subjects. This subject consisted of 40 female students and 40 male students. Data collection was done by giving a number sense test as many as 10 questions to all subjects, the correct answer was worth 1 and the wrong answer was worth 0. The results showed that the number sense abilities of female and male students were in the low category with an average percentage of correct answers. each gender is 32.50% and 27.00%.